Distinct and Overlapping Requirements for Cyclins A, B, and B3 in Drosophila Female Meiosis. - Bourouh, M.; Dhaliwal, R.; Rana, K.; Sinha, S.; Guo, Z.; Swan, A. (G3 : genes - genomes - genetics, 2016)
Meiosis, like mitosis, depends on the activity of the cyclin dependent kinase Cdk1 and its cyclin partners. Here, we examine the specific requirements for the three mitotic cyclins, A, B, and B3 in meiosis of Drosophila melanogaster We find that all three cyclins contribute redundantly to nuclear envelope breakdown, though cyclin A appears to make the most important individual contribution. Cyclin A is also required for biorientation of homologs in meiosis I. Cyclin B3, as previously reported, is required for anaphase progression in meiosis I and in meiosis II. We find that it also plays a redundant role, with cyclin A, in preventing DNA replication during meiosis. Cyclin B is required for maintenance of the metaphase I arrest in mature oocytes, for spindle organization, and for timely progression through the second meiotic division. It is also essential for polar body formation at the completion of meiosis. With the exception of its redundant role in meiotic maturation, cyclin B appears to function independently of cyclins A and B3 through most of meiosis. We conclude that the three mitotic cyclin-Cdk complexes have distinct and overlapping functions in Drosophila female meiosis.